La lectoescritura y su incidencia en el rendimiento académico de los niños y niñas del cuarto año de educación general básica de la escuela fiscal mixta “Río San Pablo” del recinto El Toquillal, cantón La Maná en el periodo lectivo 2012 - 2013 - Cunuhay Pastueña, Alexandra Paulina (2014)
The purpose of this research is to know what degree of impact literacy has on academic performance of students?, In order to suggest the use of teaching techniques to develop and optimize literacy learning in academic activities of teachers and students for which we used descriptive research field mode, the survey of teachers and students in the fourth year of basic education basic education, the results were that the property does not have a methodological guide to guide the teacher in implementing development of technical skills required by students in the area of literacy teaching staff also is adequately trained in this field of knowledge....